Nutritional Status and Nutrition-Related knowledge Among Urban Adolescent Girls in Bangladesh - Farjana, Rahman Bhuiyan; Joti, Lal Barua; Kazi, Abul Kalam (International Journal of Nutrition, 2020)
Background Nutritional status of adolescent girls is very crucial for their health and has a great impact on the quality of the next generation. The present study aimed to investigate the nutritional status and nutrition-related knowledge among urban adolescent girls in Bangladesh. Methods A cross-sectional study involving a total 500 of adolescent girls (aged 10-19) from four schools and colleges in Dhaka city. Socio-demographic, anthropometric and nutrition-related information was collected by semi-structured questionnaires. In addition, 24 hours food recall and food frequency questionnaire was used to assess the dietary intake. Results The ages of the early adolescent and late adolescent girls yrs (Mean ± SD) were 12±1 and 17±1 respectively. The mean (±SD) BMI of the early adolescent and late adolescent was 21.12±0.32 and 22.10±3.89 correspondingly. Among the early adolescent girls, the nutritional knowledge score was about 62% (moderate), 87% had a positive attitude and 72% had good practices in their daily lives. Whereas among the late adolescent girls, the nutritional knowledge score was about 57% (moderate), 90% showed a positive attitude and 61% had good practices. Among the subject, the average calorie intake was 1491 kcal, which was 24% lower than RDA. The Carbohydrate intake was lower than the RDA but the protein and fat intake was higher than the RDA. Conclusions The dietary intake of adolescent girls was found inadequate. Nutrition education and strong motivation can create positive changes in dietary intake. To understand the real phenomena of dietary intake of adolescent girls, further study is necessary to conduct with a large sample size.
Keywords: Nutritional knowledge; malnutrition; dietary pattern; adolescent girls; Bangladesh